Incidence, risk factors and outcomes of avascular necrosis occurring after humeral lateral condyle fractures. Issue 2 (March 2020) - Shabtai, Lior; Lightdale-Miric, Nina; Rounds, Alexis; Arkader, Alexandre; Pace, J. Lee
Abstract : Avascular necrosis (AVN) of the distal humerus is a known complication of lateral condyle fractures yet the specific rate of occurrence is unknown. The purposes of this study are to analyze the incidence, outcomes, and risk factors for AVN following lateral condyle fractures. A retrospective chart review of children diagnosed with a lateral condyle fracture between 2001 and 2014 at level-1 tertiary pediatric center was completed. Demographic data, Weiss classification, time from injury to surgery, operative vs. nonoperative management, open vs. closed reduction, and type of fixation were studied. For patients with radiographs consistent with AVN at any point in their care, elbow range of motion (ROM), pain, and deformity were measured at last follow up. Of the 500 patients evaluated, the incidence of AVN was 1.4%. All cases of AVN were following open reduction and percutaneous fixation ( P = 0.01) as initial treatment. Type III fractures were significantly associated with AVN ( P = 0.041). After average follow up of 59 weeks (range: 24–150 weeks), all patients regain full ROM except one patient who lacked of 15° of extension and 10° of flexion. Five patients were asymptomatic while two patients had mild pain. There was no radiographic evidence of valgus or varus deformity at final follow up. AVN following lateral condyle fractures is rare with a rate of only 1.4%. Type III fractures and open reduction were significantly associated with AVN. Provided no residual deformity and reconstitution of avascular bone, good outcomes can be expected.